Amelioration of adverse effects of heat stress using custom design shelter system and supplementing chromium propionate to growing Karan Fries calves during summer - SINGH, SUNIL; SINGH, S V; RENUKA, RENUKA; KUMAR, YOGENDRA; KUMAR, ANIL; BALIYAN, BEENAM; KUNDU, S S (The Indian Journal of Animal Sciences, 2017)
Climate change has become a threat to the sustainability of livestock systems throughout the world. Present study was carried out to evaluate the ameliorative effect of custom design shelter system and chromium propionate supplementation in crossbred calves, for which 15 growing Karan Fries crossbred calves were further divided equally into three groups based on their body weight and age. Groups 1, 2 and 3 animals were kept in an open shed (control), under custom designed shed and under custom designed shed supplemented with chromium propionate @ 0.5 mg/kg DMI through chromium propionate, respectively. These animals were fed on the fodder and concentrate (60:40) ad lib. All calves were kept under similar feeding and management schedule for 8 days under preliminary period to adapt on the diet followed by 90 days experimental period. Blood samples were collected on day 0, 45 and 90 for the analysis of biochemical parameters (cortisol, catalase, IgA and IgM) and expression of growthrelated gene (NFIL3). Results showed that the custom designed shed reduced the Tmax (32.94°C) by 3.24°C compared to the open shed (36.18°C) and improved the dry matter intake (DMI), average daily gain (ADG) and decreased water intake of growing calves of group 3 and 2 over group 1. Results further indicated lower stress(cortisol, catalase) levels and better immunity (IgA and IgM) in group 3 compared to group 2 and 1. The generelated to growth (NFIL3) showed higher expression in group 3 compared to the group 2 and 1. The improvementin body weight gain with better immunity and lower stress level in group 3 and 2 indicated beneficial effect ofcustom designed shelter system and chromium propionate supplementation to Karan Fries growing calves. Therefore, micro environment modification by shed along with chromium supplementation can be suggested as an important management practices during heat stress for crossbreed calves.